2017
DOI: 10.1016/j.aogh.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surgical and Trauma Capacity in Potosí, Bolivia

Abstract: Surgical and trauma capacity in Potosí was most limited in personnel, infrastructure, and procedures at rural facilities, with greater personnel deficiencies than previously reported. Interventions should focus on increasing the number of surgical and anesthesia personnel in rural areas, with a particular focus on the reported desire for trauma management training. Results have been made available to key stakeholders in Potosí to inform targeted quality improvement interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Despite these reports and the unfortunate but demonstrative experiences of many countries, global preparedness toward MCI is still not institutionalized by proper management plans, promoted by governments, and nor are health care personnel sufficiently trained for the challenges likely to come [8][9][10].…”
Section: However An Analysis Of the Actual Characteristics Features mentioning
confidence: 99%
“…Despite these reports and the unfortunate but demonstrative experiences of many countries, global preparedness toward MCI is still not institutionalized by proper management plans, promoted by governments, and nor are health care personnel sufficiently trained for the challenges likely to come [8][9][10].…”
Section: However An Analysis Of the Actual Characteristics Features mentioning
confidence: 99%
“…The PIPES and INTACT surveys conducted in Bolivia reported that the surgical capacity indexes (departments of Potosí and Santa Cruz) and trauma care (Potosí) of urban institutions were higher than in the rural institutions. (20,21) Likewise, over fifty percent of the surgeons and anesthesiologists in Potosí work in urban institutions; and, in the case of Santa Cruz, several rural institutions did not have an anesthesiologist available. In the Piura region, all the surgical care centers were in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 28% (16/57) of articles reference transport and logistical concerns as a barrier to trauma care [25,26,29,30,41,46,47,49,50,52,55,56,65,74,78,79] . Eight articles highlight issues with ambulances including locations of ambulance bases, time taken to deploy ambulances, time taken to reach patient, distance from hospital and traffic, all of which increase pre-hospital time.…”
Section: Transport and Logisticsmentioning
confidence: 99%
“…Fourteen articles [25,29,33,47,55,56,59,62,64,66,68,69,75,79] were assessed against the RTI item bank for risk of bias. Five articles were reviews or reports [39,44,54,76,77], and therefore could not be evaluated.…”
Section: Risk Of Biasmentioning
confidence: 99%